(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The English Romantic Movement rose to supreme eminence around 1798 withthe publication of the Lyrical Ballads. To assign a particular date to this great movement would be suffice todie hard adherents of English Literature. It was not a sudden outburst but the result of a culmination of a longgradual growth and steady development. The authors of this paper have a small desire to once again bring to ourmodern memory the saga and journey of this great movement in the gloriousannals of English Literature. It’s witha deep sense of profound tribute to the great poets of this movement that thepresenters of this paper would like to recall and revive by producing thisarticle for readers of Literature. Wehope to do justice as far as possible to apply our limited scholarship to thisbrief article.